PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA DAN KINERJA PADA PKS PT. ANDERSON UNEDO PETAPAHAN TAPUNG - Setiawan, Adi; Baharuddin , Yulizar; Azhari, Azhari; Henrizal, Henrizal; Pirmansyah, Pirmansyah (Komunitas Manajemen Kompetitif, 2024)
This study aims to analyze the Influence of Work Environment, Work Motivation and Work Discipline on Job Satisfaction and Employee Performance at the palm oil factory of PT. Anderson Unedo in Petapahan Tapung. The population in this study were all employees known to be 94 employees. The sample in this study was determined using the proportionate stratified random technique so that the number of samples was 47 respondents. Data analysis used Structural Equation Modeling (SEM) using the SmartPLS 3 application. The results of this study indicate that the work environment does not affect job satisfaction, work motivation has a significant effect on job satisfaction, the work environment does not affect employee performance, work motivation does not affect employee performance and job satisfaction has a significant effect on employee performance, while the Discipline variable must be eliminated because there is multicollinearity greater than 10